GENERATING FUNCTION FOR CLEBSCH-GORDAN-COEFFICIENTS, OF THE SUQ(2) QUANTUM ALGEBRA - Avancini, S. S.; Menezes, D. (Iop Publishing Ltd, 1993)
Some methods have been developed to calculate the su(q)(2) Clebsch-Gordan coefficients (CGC). Here we develop a method based on the calculation of Clebsch-Gordan generating functions through the use of 'quantum algebraic' coherent states. Calculating the su(q)(2) CGC by means of this generating function is an easy and straightforward task.